Обзор и сравнительный анализ основных моделей и алгоритмов многопутевой маршрутизации в мультисервисных телекоммуникационных сетях - Поповский, В. В.; Лемешко, О. В.; Мельникова, Л. И.; Андрушко, Д. В. (Прикладная радиоэлектроника, 2005)
The survey and the qualitative analysis of the basic approaches to modeling and the decision of problems of multipath routing is carried out. Probable ways of development of multipath routing in modern and perspective multiservice networks are offered.
Keywords: многопутевая маршрутизация; мультисервис; телекоммуникационная сеть